2019
DOI: 10.34133/2019/8232097
|View full text |Cite
|
Sign up to set email alerts
|

A Piezoelectric and Electromagnetic Dual Mechanism Multimodal Linear Actuator for Generating Macro- and Nanomotion

Abstract: Fast actuation with nanoprecision over a large range has been a challenge in advanced intelligent manufacturing like lithography mask aligner. Traditional stacked stage method works effectively only in a local, limited range, and vibration coupling is also challenging. Here, we design a dual mechanism multimodal linear actuator (DMMLA) consisted of piezoelectric and electromagnetic costator and coslider for producing macro-, micro-, and nanomotion, respectively. A DMMLA prototype is fabricated, and eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Besides a piezoelectric motor, an electromagnetic motor can also be found in the linear motor. Dynamic characterization test experiment prototype shows that the nanomotor can reach 2 nm under the high speed of 50 mm/s 38 …”
Section: Linear Motormentioning
confidence: 99%
See 1 more Smart Citation
“…Besides a piezoelectric motor, an electromagnetic motor can also be found in the linear motor. Dynamic characterization test experiment prototype shows that the nanomotor can reach 2 nm under the high speed of 50 mm/s 38 …”
Section: Linear Motormentioning
confidence: 99%
“…Furthermore, with the development of high-precision laser direct writing photolithography systems, such as a two-photon laser direct writing equipment, researchers directly used piezoelectric ceramics as actuators to complete the photolithography process. [35][36][37][38][39][40] Brussel et al designed a work piece with the piezoelectric ceramics, as shown in Figure 13, and the work piece possesses the advantage of high-speed positioning, high precision. Dynamic characterization experiment shows the maximum speed of prototype linear motor can exceed 100 mm/s with the movement range within 3 μm.…”
Section: Linear Motormentioning
confidence: 99%
“…The voltage outputs in Figure 5i clearly reveal that the cofired multilayer sensor leads to much bigger response as theoretical predication. With abilities to sharply decrease the drive voltage of actuation components and enhance charge re-sponse of sensing units, the innovative cofired multilayer structure is expected to effectively renovate shear-mode piezoelectric devices, such as nano shear actuators, [22] quasi-static or resonant ultrasonic motors, [15] accelerometer sensor, [19] etc.…”
Section: Enhanced Performance For Shear-type Actuators and Sensorsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] As a fundamental working mechanism, shear mode of piezoelectric elements plays indispensable roles in nanopositioning workbench, [5,15,16] distributed intelligent sensing, [17][18][19] energy conversion apparatus, [20,21] and other electromechanical devices. [14,22,23] However, conventional excitation methods of shear mode always rely on expensive and brittle piezoelectric single crystals [15][16][17][18][19] (d 36 mode) or bulk ceramics [14,22,24,25] (mainly d 15 mode), which all inevitably require high operate voltages to offer substantial displacement outputs and lead to poor service robustness from mechanical fragility or easy domain switching problems. To realize shear-type piezoelectric elements with efficient outputs compatible with modern integrated microelectronics, [5,6,14] these tough obstacles are urgently expected to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the demand of long travel range and nanometer resolution at the same time, many techniques have been developed to amplify or accumulate the displacement of the piezoelectric actuator, including the macro-micro dual drive principle [ 7 , 8 ], the inchworm drive principle [ 9 ], a piezoelectric ultrasonic motor [ 10 , 11 ], and the stick-slip drive principle [ 12 , 13 ]. Stages based on the macro-micro dual drive principle usually have large dimensions, making them unable to be used in many applications of limited space [ 14 ]. The size of an inchworm drive stage is also large, and it needs to be manufactured and assembled precisely [ 15 ].…”
Section: Introductionmentioning
confidence: 99%